KEEFEKTIFAN TEKNIK BEHAVIOR CONTRACT UNTUK MENGURANGI PERILAKU MEMBOLOS SISWA SMK PONDOK PESANTREN ABU DZARRIN BOJONEGORO - Zeti Novitasari; Hilmy Aliriad; Khusnul Khotimah (Jurnal Ilmiah Hospitality, 2020)
Ditching is one of the behaviors of a student or student who does not enter school or does not enter class hours, at the beginning of the lesson until the end of school hours. Without the knowledge of the school or from the parents, without a clear statement or permit. And is done to achieve a goal. The purpose of this study was to determine the effectivenessof the behavior contracts techniques to reduce truant behavior in vocational student. This researcher uses the design is one group pre test and post test design. Each group consisted of 5 students who were netted with high truant behavior. The instruments used were truant scale, self relf reflection sheet and observation guidelines. Data analysis techniques used in the study through the main analysis to test the research hypothesis using non-parametric statistical tests, namely Cronbach’s in each group using Wilcoxon test. The results of the research are based on the output of “ test statistics”, known asymp.sig. (2-tailed) worth 0.043. because the value of 0.043 is smaller than 0.05, with an average percentage of 66.66% in the pre test and 39.28% in the post test it can be concluded that “ Ha is accepted” shows the technique of behavior conracts can reduce truant behavior of students.